O2-dependent incapacitation of the Salmonella pathogenicity island 1 repressor HilE - Walter, Steffi; Schatz, Valentin; Petzold, Jana; Schmidt, Christiane; Hoffmann, Stefanie; Jantsch, Jonathan; Gerlach, Roman G. (Frontiers in Cellular and Infection Microbiology, 2025)
For successful colonization, pathogenic bacteria need to adapt their metabolism and virulence functions to challenging environments within their mammalian hosts that are frequently characterized by low oxygen (O2) tensions. Upon oral ingestion, the human pathogen Salmonella enterica serovar Typhimurium (S. Typhimurium) is exposed to changing O2 and pH levels. Low concentrations of O2, which can enhance the virulence of enteroinvasive pathogens, facilitate the expression of the type three secretion system (T3SS-1) encoded by the Salmonella pathogenicity island 1 (SPI-1) that is critical for enteroinvasion and pathogenicity of S. Typhimurium. To study the impact of key environmental cues of the intestine when Salmonella encounter enterocytes, we established an in vitro growth model, which allows shifting the concentration of O2 from 0.5% to 11% and the pH from 5.9 to 7.4 in the presence of acetate and the alternative electron acceptor nitrate. Compared to normoxia, hypoxia elevated the expression of SPI-1 genes encoding T3SS-1 translocators and effectors, which resulted in higher invasion and effector translocation in epithelial cells. While hypoxia and pH shift only marginally altered the gene expression of SPI-1 regulators, including the SPI-1 repressor hilE, hypoxia and pH shift completely incapacitated HilE in a post-translational manner, ultimately promoting SPI-1 activity. From these findings, we conclude that O2-dependent HilE function allows for ultrasensitive adaptation of SPI-1 activity in environments with varying O2 availability such as the intestinal tract.